(untitled) (International Journal of Nursing Education, 2020)
Objective: The aim of the study was to determine the prevalence of Dementia among Elderly and to associatethe level of Dementia with their Demographic Variables.Method: Quantitative approach and non-experimental descriptive research design was used. The datacollection included three parts. Part A: Demographic variables, Part B: Four point rating scale to assess theLevel of Dementia among elderly. A total of 100 students who fulfilled the inclusion criteria were chosen assamples using non-probability convenient sampling technique. The study was conducted at SRM Generalhospital, Kattankulathur.Results: The data were analyzed and interpreted based on the objectives using descriptive and inferentialstatistics. The study concluded that 28 (28%) of them have same than Normal level of Dementia; 50 (50%)have Worse than Normal level of Dementia; and 22 (22%) have Much Worse than Normal level of Dementiaand there is association between the “Age, Education, Occupation, Family Income, Residence and No ofChildren with the “levels of Dementia.Conclusion: Dementia is progressive brain dysfunction which result in a restriction of daily activities. Theearly stage of dementia is often overlooked and incorrectly labeled as normal old age outcomes.